Perspectives of Hearing Parents of Deaf Children on Learning Kenyan Sign Language - and Ogada Luchivya, Rosemary; Mboya Omolo, Tom; Anyango Onditi, Sharon (2022)
Purpose: The purpose of this study was to find out the challenges faced in learning Kenyan sign language from the perspective of hearing parents of deaf learners. Methodology: This study employed case study design, qualitative research approach adopting the interpretive paradigm. The researchers used a purposive sampling strategy to create a study sample of 177 people. Interview schedules, Focus Group Discussion guidelines, and Document Analysis guides were used to collect data. The data was transcribed, coded, and organized into themes before being reported. Findings: The findings revealed that parents faced three major challenges when learning Kenyan sign language: it was too difficult to learn, it was too expensive to learn, and institutions for parents to learn in were not readily available. Unique Contribution to Theory, Practice and Policy: The study's recommendations were that hearing parents of children with hearing impairments be supported in the process of learning Kenyan sign language and that parents make deliberate efforts to learn Kenyan sign language and other modes of communication in order to communicate with their children with hearing impairments.